CCR5 in recruitment and activation of myeloid-derived suppressor cells in melanoma - Umansky, Viktor; Gebhardt, Christoffer; Utikal, Jochen (Cancer immunology immunotherapy, 2017)
Malignant melanoma is characterized by the development of chronic inflammation in the tumor microenvironment, leading to the accumulation of myeloid-derived suppressor cells (MDSCs). Using ret transgenic mouse melanoma model, we found a significant migration of MDSCs expressing C-C chemokine receptor (CCR)5 into primary tumors and metastatic lymph nodes, which was correlated with tumor progression. An increased CCR5 expression on MDSCs was associated with elevated concentrations of CCR5 ligands in melanoma microenvironment. In vitro experiments showed that the upregulation of CCR5 expression on CD11b+Gr1+ immature myeloid cells was induced by CCR5 ligands, IL-6, GM-CSF, and other inflammatory factors. Furthermore, CCR5+ MDSCs infiltrating melanoma lesions displayed a stronger immunosuppressive pattern than their CCR5− counterparts. Targeting CCR5/CCR5 ligand signaling via a fusion protein mCCR5-Ig, which selectively binds and neutralizes all three CCR5 ligands, increased the survival of tumor-bearing mice. This was associated with a reduced migration and immunosuppressive potential of tumor MDSCs. In melanoma patients, circulating CCR5+ MDSCs were increased as compared to healthy donors. Like in melanoma-bearing mice, we observed an enrichment of these cells and CCR5 ligands in tumors as compared to the peripheral blood. Our findings define a critical role for CCR5 not only in the recruitment but also in the activation of MDSCs in tumor lesions, suggesting that novel strategies of melanoma treatment could be based on blocking CCR5/CCR5 ligand interactions.